Effects of Functional Electrical Stimulation Lower Extremity Training in Myotonic Dystrophy Type I: A Pilot Controlled Study. (November 2016) - Cudia, Paola; Weis, Luca; Baba, Alfonc; Kiper, Pawel; Marcante, Andrea; Rossi, Simonetta; Angelini, Corrado; Piccione, Francesco
ABSTRACT: Objective: Functional electrical stimulation (FES) is a new rehabilitative approach that combines electrical stimulation with a functional task. This pilot study evaluated the safety and effectiveness of FES lower extremity training in myotonic dystrophy type 1. Design: This is a controlled pilot study that enrolled 20 patients with myotonic dystrophy type 1 over 2 years. Eight patients (age, 39–67 years) fulfilled the inclusion criteria. Four participants performed FES cycling training for 15 days (one daily session of 30 minutes for 5 days a week). A control group, matched for clinical and genetic variables, who had contraindications to electrical stimulation, performed 6 weeks of conventional resistance and aerobic training. The modified Medical Research Council Scale and functional assessments were performed before and after treatment. Cohen d effect size was used for statistical analysis. Results: Functional electrical stimulation induced lower extremity training was well tolerated and resulted in a greater improvement of tibialis anterior muscle strength ( d = 1, 583), overall muscle strength ( d = 1, 723), and endurance ( d = 0, 626) than conventional training. Conclusions: Functional electrical stimulation might be considered a safe and valid tool to improve muscle function, also in muscles severely compromised in which no other restorative options are available. Confirmation of FES efficacy through further clinical trials is strongly advised.